Cellular telephone use and the risk of brain tumors: update of the UK Million Women Study - Schüz, J; Pirie, K; Reeves, GK; Floud, S; Beral, V (Oxford University Press, 2022)
Background: The ongoing debate of whether use of cellular telephones increases the risk of developing a brain tumor was recently fueled by the launch of the fifth generation of wireless technologies. Here, we update follow-up of a large-scale prospective study on the association between cellular telephone use and brain tumors.